NIGERIA'S FOREIGN POLICY AND TRANSBORDER CRIME: AN OVERIEW - OWUDA RASHIDA LAMIDI (International Studies Journal)
Transnational crime affects countries' internal security and foreign policy in many ways. This study examines Nigeria's foreign policy and transborder crime's considerable impact. West African nation Nigeria faces drug, human, gun, and cybercrime. These criminal operations threaten the nation's security, diplomatic relations, and global reputation. Nigeria's foreign policy has emphasised non-interference, regional collaboration, and international law. However, rising transborder crime has forced Nigeria to change its policies and become more proactive and collaborative internationally. Multifaceted links exist between transborder crime and foreign policy. First, transborder crime in Nigeria affects its economy and international relations. Diplomatic efforts aim to foster economic growth and regional stability. Transborder crime in Nigeria threatens human security, especially owing to human trafficking and illegal migration. The nation's foreign policy has stressed engagement with international institutions and neighbouring nations to address these acts' root causes. Cross-border crime and terrorism further complicate Nigeria's foreign policy. The dissemination of weaponry by criminal trafficking networks boosts insurgent factions. Nigeria works with neighbours and friends to stop the spread of weapons and fight terrorism. These efforts suggest a stronger, more coordinated foreign policy approach to transnational security. Transborder crime considerably and diversely impacts Nigeria's foreign policy. Illegal actions necessitate a planned and flexible diplomatic strategy. Nigeria's response focuses on regional cooperation, economic growth, and security through bilateral and multilateral relations. While fighting transborder crime, the nation's foreign policy evolution shows its commitment to addressing transnational threats' complex issues.